2020
DOI: 10.1038/s41598-020-57560-3
|View full text |Cite|
|
Sign up to set email alerts
|

A Small Compound Targeting Prohibitin with Potential Interest for Cognitive Deficit Rescue in Aging mice and Tau Pathology Treatment

Abstract: Neurodegenerative diseases, including Alzheimer's and Parkinson's disease, are characterized by increased protein aggregation in the brain, progressive neuronal loss, increased inflammation, and neurogenesis impairment. We analyzed the effects of a new purine derivative drug, PDD005, in attenuating mechanisms involved in the pathogenesis of neurodegenerative diseases, using both in vivo and in vitro models. We show that PDD005 is distributed to the brain and can rescue cognitive deficits associated with aging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…The adenine derivative PDD005 is a PHB ligand that rescues cognitive deficits associated with aging in mice. 42 It also alleviates neurogenesis deficiency and inhibits neuro-inflammation, confirming PHBs as emerging therapeutic targets against neurodegenerative diseases.…”
Section: Prohibitins and Their Ligandsmentioning
confidence: 93%
“…The adenine derivative PDD005 is a PHB ligand that rescues cognitive deficits associated with aging in mice. 42 It also alleviates neurogenesis deficiency and inhibits neuro-inflammation, confirming PHBs as emerging therapeutic targets against neurodegenerative diseases.…”
Section: Prohibitins and Their Ligandsmentioning
confidence: 93%
“…Furthermore, PHBs are important in the regulation of cristae morphology, reactive oxygen species formation, or mitophagy [ 4 , 5 , 11 ]. Different molecules have been described to interact with PHBs [ 12 , 13 , 14 ]. We previously demonstrated that PHBs are required for the proapoptotic effect of fluorizoline in mouse embryonic fibroblasts as well as in HEK293T and U2OS human cell lines [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, an analogue, PDD005 (28), was found to display opposite effects [96]. Indeed it rescues cognitive deficits associated with aging in mice.…”
Section: Adenine Derivatives Aftin-4 and Pdd005mentioning
confidence: 99%